Narrating space and motion in contemporary Asian British novels: a cultural narratology of motion - Matschi, Alexander Franz; Justus Liebig University Giessen (My University, 2015)
This study develops a context-oriented narratological semantics for the narrative enactment of human motion in short, a cultural narratology of motion in contemporary Asian British novels. Assuming that literary texts are inextricably interlocked with their cultural contexts, it elaborates a trialectics of motion, that is, a heuristic theoretical model designed to account for the fundamental multidimensionality of human motion in extratextual cultural reality and literary representation. More precisely, this trialectics conceptualizes the cultural and literary phenomenon of human motion as emerging from the combinatorial interplay of spatiality, agency and temporality. This study defines the combinatorial interplay of these three constitutive dimensions in extratextual cultural and narrative configurations of human motion as ontological vectoriality. The ontological concept of vectoriality is complemented by a narratological conceptualization of vectoriality, defined as the emergence of the narrative enactment of human motion from the combinatorial interplay of what Nünning (cf. 2008a: 19-26) refers to as the three constitutive dimensions of literary representation: the paradigmatic axis of selection, the syntagmatic axis of combination and the discursive axis of perspectivization. Building on cognitive narratology, this study argues that in literary texts, narratological vectoriality generates the illusion of ontological vectoriality that is, of a character moving across space over time in the reader s mind.The cultural narratology of motion further differentiates between different types of narrative vectors namely intended, experienced and imagined ones in order to capture the ontological complexity of the narrative enactment of real-and-imagined (sensu Soja 1996) movements in three contemporary Asian British novels analysed in detail: The Impressionist (Kunzru 2002), A Life Apart (Mukherjee 2008) and The Pleasure Seekers (Doshi 2010). Due to the frequently minimalistic mode deployed for the narrative representation of transnational migrations in these novels, this study assigns particular saliency to characters mental mobility as one crucial resource for the semanticization of such migratory movements. In addition, the study brings together cultural topology and postclassical narratology in its reconceptualization of storyworld topologies as narratopologies, that is, as agentive space-time configurations emerging from the narrative representation of myriad real-and-imagined movements across the storyworld. In the absence of detailed accounts of the migratory movements themselves, such narratopologies constitute a second major resource for the cultural semanticization of the protagonists transnational migrations from India to Britain (or vice versa). All in all, this study shows that the interdependent narrative representation of space and motion in contemporary Asian British novels can be made accessible to contextualized narratological scrutiny by combining a cultural trialectics of motion with a vector-based narratological model.

Die vorliegende Studie entwickelt eine kontextorientierte narratologische Semantik zur Analyse der narrativen Inszenierung menschlicher Bewegung kurz: eine kulturelle Narratologie der Bewegung in zeitgenössischen Asian British novels. Aufbauend auf der Einsicht in die komplexe Verflochtenheit literarischer Texte mit ihren kulturellen Kontexten, arbeitet die Studie eine Trialektik der Bewegung aus, also ein heuristisches theoretisches Modell, das der Multidimensionalität menschlicher Bewegung sowohl in der extratextuellen kulturellen Realität als auch in der literarischen Repräsentation Rechnung trägt. Konkret konzeptualisiert diese Trialektik die Entstehung des kulturellen und literarischen Phänomens menschlicher Bewegung als Resultat des kombinatorischen Zusammenspiels von Räumlichkeit, Agency und Zeitlichkeit. Das Zusammenwirken dieser drei konstitutiven Dimensionen in extratextuellen kulturellen und narrativen Konfigurationen menschlicher Bewegung definiert diese Studie als ontologische Vektorialität. Das ontologische Vektorialitätskonzept wird ergänzt durch eine narratologische Konzeptualisierung von Vektorialität, definiert als die Entstehung der narrativen Inszenierung menschlicher Bewegung aus dem kombinatorischen Zusammenspiel der drei konstitutiven Dimensionen literarischer Darstellung nach Nünning (vgl. 2008a: 19-26): der paradigmatischen Achse der Selektion, der syntagmatischen Achse der Kombination und der diskursiven Achse der Perspektivierung. Im Sinne der kognitiven Narratologie argumentiert diese Studie, dass narratologische Vektorialität in literarischen Texten die Illusion ontologischer Vektorialität also einer sich durch Raum und Zeit bewegenden Figur in der Vorstellung des Lesers erzeugt.Die in dieser Studie entwickelte kulturelle Narratologie der Bewegung differenziert zwischen verschiedenen Typen narrativer Vektoren intended, experienced and imagined vectors, um die ontologische Komplexität der narrativen Inszenierung real-und-imaginierter (sensu Soja 1996) Bewegungen in drei im Detail analysierten Asian British novels zu erfassen: The Impressionist (Kunzru 2002), A Life Apart (Mukherjee 2008) und The Pleasure Seekers (Doshi 2010). Aufgrund des häufig minimalistischen Modus der narrativen Repräsentation transnationaler Migrationen in den Romanen misst diese Studie der mental mobility von Figuren als einer entscheidenden Ressource für die Semantisierung solcher Migrationsbewegungen besondere Bedeutung zu. Darüber hinaus kombiniert diese Arbeit Ansätze der kulturellen Topologie und der postklassischen Narratologie in ihrer Re-konzeptualisierung von Topologien der erzählten Welt als Narratopologien, das heißt, als agentive space-time configurations, die aus der narrativen Darstellung einer Vielzahl real-und-imaginierter Bewegungen durch die erzählte Welt hervorgehen. In Folge des Verzichts auf detaillierte Schilderungen der Migrationsbewegungen selbst stellen solche Narratopologien eine zweite wichtige Ressource für die kulturelle Kontextualisierung der transnationalen Migrationen der Protagonisten von Indien nach Großbritannien (oder in umgekehrter Richtung) dar. Alles in allem zeigt diese Studie, dass die interdependente narrative Inszenierung von Raum und Bewegung in zeitgenössischen Asian British novels durch die Kombination einer kulturwissenschaftlichen Trialektik der Bewegung mit einem vektorbasierten narratologischen Modell der kontextualisierten narratologischen Analyse zugänglich gemacht werden kann.
Keywords: Narratologie; Bewegung; Migration; Vektor; Topologie; Narratology; Motion; Migration; Vector; Topology; ddc:420